Identifying proteins in the cell by tagging techniques for cryo-electron microscopy. (18th February 2022) - Kikkawa, Masahide; Yanagisawa, Haruaki
Abstract: Cryo-electron microscopy (cryo-EM) is currently expanding its application from molecular structures to cellular structures. The cellular environment is heterogeneous, containing many different proteins, and very crowded. This environment is in sharp contrast to the specimens for single particle analysis, by which purified homogeneous samples are analyzed. To answer biological questions from the structural studies of cells, it is crucial to identify biological molecules (typically, proteins) of interest and tagging is becoming the critical technique for cryo-EM. In this review, we explain the requirements for tags and review recent advances of tagging and identification methods for cryo-EM.